Moderate red wine consumption is associated with a lower prevalence of the metabolic syndrome in the PREDIMED population. (7th July 2015) - Tresserra-Rimbau, Anna; Medina-Remón, Alexander; Lamuela-Raventós, Rosa M.; Bulló, Monica; Salas-Salvadó, Jordi; Corella, Dolores; Fitó, Montserrat; Gea, Alfredo; Gómez-Gracia, Enrique; Lapetra, José; Arós, Fernando; Fiol, Miquel; et al.
Abstract : Previous studies on the association between alcohol intake and the development of the metabolic syndrome (MetS) have yielded inconsistent results. Besides, few studies have analysed the effects of red wine (RW) consumption on the prevalence of the MetS and its components. As moderate RW drinkers have a better lipid profile and lower incidence rates of diabetes, hypertension and abdominal obesity, all components of the MetS, it was hypothesised that moderate RW consumption could be associated with a lower prevalence of the MetS. In the present cross-sectional study of 5801 elderly participants at a high cardiovascular risk included in the PREDIMED (Prevención con Dieta Mediterránea) study, 3897 fulfilled the criteria of the MetS at baseline. RW intake was recorded using a validated 137-item FFQ. Multiple logistic regression analysis was carried out to estimate the association between RW intake and the prevalence of the MetS. Compared with non-drinkers, moderate RW drinkers ( ≥ 1 drink/d) were found to have a reduced risk of prevalent MetS (OR 0·56, 95 % CI 0·45, 0·68; P < 0·001), a lower risk of having an abnormal waist circumference (OR 0·59, 95 % CI 0·46, 0·77; P < 0·001), low HDL-cholesterol concentrations (OR 0·42, 95 % CI 0·32, 0·53; P < 0·001), high blood pressure (OR 0·28, 95 % CI 0·17, 0·45; P < 0·001) and high fasting plasma glucose concentrations (OR 0·67, 95 % CI 0·54, 0·82; P < 0·001) after adjusting for several confounders. This association was found to be stronger in female participants, in participants aged < 70 years and in participants who were former or current smokers. No significant association was found between RW intake ( ≥ 1 drink/d) and TAG concentrations. In conclusion, moderate RW consumption is associated with a lower prevalence of the MetS in an elderly Mediterranean population at a high cardiovascular risk.